Exploration and Application of Project‐Based Teaching Integrating Scientific Research Achievements in Electronic Comprehensive Design Course - Ma, Hongxing; Li, Lin; Ma, Yun; Liu, Xuan; Yang, Shanglin (Computer applications in engineering education, 2025)
ABSTRACT Effective teaching content design, implementation methods, and a scientifically rigorous evaluation system are essential for cultivating students' innovative practical abilities and enhancing teaching quality in the electronic comprehensive design course. Addressing the challenge of ineffective integration between theory and practice in the undergraduate electronic engineering in Chinese universities, this study leverages the framework of engineering education certification to explore a project‐based teaching model that integrates scientific research achievements into the electronic comprehensive design course. This study aims to solve the key limitations of traditional project‐based teaching, specifically its disconnect from cutting‐edge technology and lack of dynamic feedback, by constructing a “research feedback teaching” mechanism. A three‐dimensional screening framework—comprising technical feasibility, teaching adaptability, and social demand correlation—is developed to decompose complex scientific research projects into progressive teaching tasks that span basic skills, unit design, and system engineering, thereby enabling a comprehensive, full‐process electronic design practice. To ensure effective assessment, the study integrates process‐oriented (45%), outcome‐oriented (45%), and innovative‐driven (10%) evaluation methods, complemented by inter‐group peer assessments, multi‐party reviews, and user experience feedback. This approach establishes an “evaluation‐feedback‐improvement” loop, effectively addressing the issue of feedback delays observed in traditional CDIO and NEET models. Empirical evidence from the teaching practice between 2018 and 2020 demonstrates that the adoption of this model significantly improve students’ overall performance (average score increased from 82.73 to 85.67, p < 0.05), and enhanced their innovative thinking and interdisciplinary problem‐solving abilities by 23%. Based on these findings, this study proposes further policy recommendations, including the establishment of a dedicated fund for scientific research into teaching, the incorporation of progressive project‐based learning practices into engineering certification standards, and the development of a replicable closed‐loop framework for engineering education reform.